The Role of Cancer Stem Cells in Radiation Resistance - Arnold, Christoph Reinhold; Mangesius, Julian; Skvortsova, Ira-Ida; Ganswindt, Ute (Frontiers in Oncology, 2020)
Cancer stem cells (CSC) are a distinct subpopulation within a tumor. They are able to self-renew and differentiate and possess a high capability to repair DNA damage, exhibit low levels of reactive oxygen species (ROS), and proliferate slowly. These features render CSC resistant to various therapies, including radiation therapy (RT). Eradication of all CSC is a requirement for an effective antineoplastic treatment and is therefore of utmost importance for the patient. This makes CSC the prime targets for any therapeutic approach. Albeit clinical data is still scarce, experimental data and first clinical trials give hope that CSC-targeted treatment has the potential to improve antineoplastic therapies, especially for tumors that are known to be treatment resistant, such as glioblastoma. In this review, we will discuss CSC in the context of RT, describe known mechanisms of resistance, examine the possibilities of CSC as biomarkers, and discuss possible new treatment approaches.